Building dictatorships under Axis rule
1 online resource.
Keywords: "This book offers a broad comparative perspective on regime building under Axis rule during the Second World War, exploring case studies in Europe and Asia. Military occupation represents the highest degree of political, social and economic control over an occupied state and its society. This collective book analyses how the three poles of Axis rule, Nazi Germany, Italian Fascism and Authoritarian Japan, lead the dynamics of institution-building of political regimes of occupation under their direct or indirect control. The contributions examine how the ideological, political and economic relationship between the occupying forces and different segments of national and local elites were present in the institutional crafting of new regimes. Military occupation opened a window of opportunity for the takeover of power by different segments of these authoritarian elites and the tension and forced pacts between different projects of institutionalization of dictatorships were a clear sign of this dynamic process. In this context, the debates and the praxis of the construction of new dictatorial political systems are analysed, looking to identify the design of their institutions, the segments of the political elites that hegemonize them, the diffusion and promotion models present, and the attitudes of the Axis powers before them. This volume is ideal for all those interested in the study of War, Dictatorships, and the global history and politics of Fascism"--